Evaluation of M2 Wheat (Triticum aestivum L.) Mutants for Yield and its Contributing Traits - Saima Bano; Zahoor Ahmed Soomro; Arshad Ali Kaleri; Rabab Akram; Sajida Nazeer; Abdul Latif Laghari; Irfan Ali Chandio; Rahila Keerio; Niaz Ahmed Wahocho (Journal of Basic & Applied Sciences, 2017)
The present research was conducted to evaluate the M2 wheat mutant population for yield and its contributing traits. The experiment was conducted at Nuclear Institute of Agriculture (NIA), Tando Jam, during rabi season 2015-2016, in split plot design with three replications. Two wheat varieties (T. D-1 and ESW-9525) were treated with different levelsof gamma rays (150Gy, 200Gy, 250Gy, 300Gy and control) from NIMRA (Nuclear Institute of Medicine and Radiotherapy), Jamshoro. The mutated plants were evaluated along with parental lines (control) for yield and its contributing traits under field conditions. Genetic parameters viz., mean performance, were calculated such as days to 75 % heading, days to 75 % maturity, plant height (cm), spikelets spike-1 and spike length (cm). Mean square showed that there were significant differences between wheat varieties for days to 75% heading, days to 75% maturity, plant height (cm), spikelets spike-1 and spike length (cm) treatments of gamma radiation caused significant variation in all the traits studied. The interaction between treatments × varieties showed highly significant differences for the entire traits indicating that varieties responded differently for radiation treatments. Mean performance forspike length indicated that the longer spike (11.52 cm) was observed in T.D-1 at treatment four (T4=250 Gy) and treatment two (150 Gy) in ESW-9525 . Whereas, the shortest spike (10. 83 cm) wasobserved in the variety T.D-1 under control. The results regarding maximum mean performance ofspikelets spike-1 (24. 74) were recorded in ESW-9525 under treatment five at 300 Gy whereas the minimumvalue forspikelets spike-1 (18.76) were observed in T.D-1 under T1 (18.76) at 0 Gy and T4 at 250 Gy.